Shirts Powdered Red : Haudenosaunee Gender, Trade, and Exchange across Three Centuries - Kane, Maeve, 1986- (Book collections on Project MUSE., 2023)
"Haudenosaunee (Iroquois) women in what is now New York and Quebec used trade with Europeans and Americans from the seventeenth century through the nineteenth century to reinforce their cultural and political sovereignty"